Clinical Untargeted Metabolomics as a Functional Screen to Improve Variant Classification. Issue 4 (10th April 2023) - Gijavanekar, Charul; Elsea, Sarah H.
Abstract: With the rapid increase in clinical exome and genome sequencing, the number of variants of uncertain significance (VUS) that are reported continues to rise, which poses a significant barrier to interpretation of genetic findings. For metabolic disorders, biochemical testing can help alleviate this burden of variant interpretation by providing functional validation of uncertain genetic findings in many cases. However, a major limitation of traditional biochemical testing is the targeted, narrow range of analytes clinically available, resulting in delays in diagnosis if testing is negative. Untargeted metabolomic screening offers higher diagnostic yield and assays for thousands of metabolites across multiple metabolic pathways in a single test, saving time and resources for patients, families, and physicians. When integrated with exome or genome sequencing, untargeted metabolomic screening improves diagnostic outcomes by providing functional validation of genetic findings, particularly for VUS. Here, we present representative cases across the breadth of metabolic pathways as examples of the utility of metabolomics in genomic variant classification. © 2023 Wiley Periodicals LLC.